Treating severe and enduring anorexia nervosa: a randomized controlled trial. Issue 12 (December 2013) - Touyz, S.; Le Grange, D.; Lacey, H.; Hay, P.; Smith, R.; Maguire, S.; Bamford, B.; Pike, K. M.; Crosby, R. D.
<x content-type="archive" xml:space="preserve">Abstract</x> Background There are no evidence-based treatments for severe and enduring anorexia nervosa (SE-AN). This study evaluated the relative efficacy of cognitive behavioral therapy (CBT-AN) and specialist supportive clinical management (SSCM) for adults with SE-AN. Method Sixty-three participants with a diagnosis of AN, who had at least a 7-year illness history, were treated in a multi-site randomized controlled trial (RCT). During 30 out-patient visits spread over 8 months, they received either CBT-AN or SSCM, both modified for SE-AN. Participants were assessed at baseline, end of treatment (EOT), and at 6- and 12-month post-treatment follow-ups. The main outcome measures were quality of life, mood disorder symptoms and social adjustment. Weight, eating disorder (ED) psychopathology, motivation for change and health-care burden were secondary outcomes. Results Thirty-one participants were randomized to CBT-AN and 32 to SSCM with a retention rate of 85% achieved at the end of the study. At EOT and follow-up, both groups showed significant improvement. There were no differences between treatment groups at EOT. At the 6-month follow-up, CBT-AN participants had higher scores on the Weissman Social Adjustment Scale (WSAS; p = 0.038) and at 12 months they had lower Eating Disorder Examination (EDE) global scores (p = 0.004) and higher readiness for recovery (p = 0.013) compared to SSCM. Conclusions Patients with SE-AN can make meaningful improvements with both therapies. Both treatments were acceptable and high retention rates at follow-up were achieved. Between-group differences at follow-up were consistent with the nature of the treatments given.